Customer Experience, Brand Image, dan Perceived Value: Pengaruhnya Terhadap Kepuasan Pelanggan Netflix Melalui Mediasi Keputusan Pembelian Mahasiswa FISIP UNTAG Surabaya - Agata Winda Christianti; Ayun Maduwinarti; Awin Mulyati (Politeknik Kampar, 2025)
This study aims to examine the influence of customer experience, brand image, and perceived value on customer satisfaction through purchase decision as a mediating variable. The research was conducted on students of the Faculty of Social and Political Sciences at Universitas 17 Agustus 1945 Surabaya who use the Netflix application. A quantitative approach was used with a questionnaire distributed to 100 respondents. The data were analyzed using Structural Equation Modeling with the Partial Least Squares (PLS) method. The findings reveal that customer experience, brand image, and perceived value significantly influence purchase decision and customer satisfaction. Moreover, purchase decision is proven to mediate the relationship between the independent variables and customer satisfaction. These results highlight the importance of enhancing user experience, building a strong brand image, and delivering value perception to increase customer satisfaction through more informed purchase decisions. The study contributes to understanding consumer behavior in the digital entertainment industry, particularly among students as a major user segment.